INFLUENCE THE SOCIAL CAPITAL ON PERFORMANCE OF AGRICULTURAL EXTENSION OFFICERS FOR AGRICULTURAL EXTENSION IN KONAWE REGENCY - Mappasomba, Musadar; Salahuddin, Salahuddin; Malik, Nurhayu (Jurusan Penyuluhan Pertanian FP UHO, 2026)
This study aimed to examine: (1) how is the social capital on extension officers in agricultural extension; how is performance of extension officers in agricultural extension; and (3) how does influence the social capital on the performance of extension officers in agricultural extension in Konawe Regency. The research sample comprised the entire population of agricultural extension officers in agricultural extension who are State Civil Apparatus (ASN) in Konawe Regency, totaling 113 individuals, with sampling conducted through a census method. The research variables consist of independent variables, namely the social capital of agricultural extension officers and dependent variables, namely the performance of agricultural extension officers in agricultural extension. Data analysis for this research employs both descriptive and inferential statistics. Descriptive statistics are utilized to outline the characteristics of the variables, where as inferential statistical analysis is employed to investigate the influences variable of social capital of agricultural extension officers on the performance of agricultural extension officers in agricultural extension. The inferential statistical technique applied in this research is Simple Linier Regression Analysis. The results of the study showed that the social capital of agricultural extension officers is in the good category. The research results also showed that the performance of agricultural extension workers is in the good category. The results of the study also show that the social capital of agricultural extension officers has a significant positive effect on the performance of agricultural extension officers in agricultural extension in Konawe Regency. Increasing the social capital for agricultural extension officers will improve the performance of agricultural extension officers in agricultural extension.